High quality AlN with uniform in-plane strain on nano-patterned AlN templates achieved by preset strain modulation. (2nd December 2021) - Liu, Baiyin; Xu, Fujun; Wang, Jiaming; Lang, Jing; Zhang, Na; Fang, Xuzhou; Wang, Liubing; Yang, Xuelin; Kang, Xiangning; Wang, Xinqiang; Qin, Zhixin; Ge, Weikun; et al.
Abstract: High-quality AlN with uniform in-plane strain has been attempted with preset strain modulation on nano-patterned AlN templates (NPATs). It is found that this strain preset frame can effectively improve both the tilt and twist features of AlN on NPATs, further greatly decreasing threading dislocation density. More importantly, the AlN epilayer after completing coalescence can maintain the in-plane uniform compressive strain. Adopting AlN templates achieved in this scheme, the chip-on-wafer light output power (LOP) of AlGaN light-emitting diode (LED) reaches 10.2 mW at 100 mA with single emission peak at 280 nm, which increases by 22.3% than the LOP of LED device without adopting this strain preset frame.